BERMAIN SEBAGAI KEBUTUHAN DAN STRATEGI PENGEMBANGAN DIRI ANAK - Anita Yus (JIV-Jurnal Ilmiah Visi, 2013)
Playing games is a part of the childrenâ€™s life. In playing games the children are exploring and understanding their world. This article discusses how playing games can be used in childrenâ€™s education. The children can play anywhere and anytime they want. The context, place, and time will determine the forms, activities, and game content. In playing games, the children plan, concentrate on doing certain tasks, solve problems, and express their ideas. This article concludes that playing games can be designed and used as a strategy of the children self development. Learning activities to be done by the children are integrated in playing activities. These activities facilitate the children to gain new knowledge and experience.